Post-Soviet affairs - Joint Committee on Soviet Studies (U.S.); Social Science Research Council (U.S.); American Association for the Advancement of Slavic Studies. (V.H. Winston & Son, 1992)
Continues: Soviet economy (Silver Spring, Md.), ISSN 0882-6994.Founded in association with The Joint Committee on Soviet Studies of the American Council of Learned Societies and the Social Science Research Council.